THE EFFECT OF PRENATAL MASSAGE ON REDUCING BACK PAIN IN PREGNANT WOMEN IN THE THIRD TRIMESTER AT THE PEBAYURAN COMMUNITY HEALTH CENTER IN 2023 - Sabirah, Anisa; Rismayanti, Tetin (HEARTY, 2025)
Background: Pregnancy is a natural physiological process that occurs in women. However, health workers, especially midwives, who help pregnant women must provide care that is in accordance with their needs and authority. Based on a preliminary study conducted at the Pebayuran Community Health Center, Bekasi Regency, there were 112 pregnant women and 37 (33%) of them were third trimester pregnant women who experienced back pain. . Based on the results of interviews with midwives on duty at the community health center, it was found that treatment of back pain in pregnant women in the third trimester was carried out by counseling that back pain that occurs is a normal condition experienced by pregnant women at advanced stages of pregnancy, from interviews with midwives at the community health center. stated that he had never had prenatal massage because pregnant women in the third trimester were afraid it would disrupt the development of the fetus. Research Objective: To determine the effect of prenatal massage on reducing back pain in pregnant women in the third trimester at the Pebayuran Community Health Center. Research Method: This research used quasi experimental with purposive sampling with a sample of 30 people. Data techniques include univariate analysis using frequency distributions and bivariate analysis using statistical calculations from the SPSS program. Research Method: This type of research is experimental research, namely research by carrying out experimental activities. The design used in this research is a pre-posttest control group design carried out at the Pebayuran Community Health Center involving pregnant women in the third trimester as research subjects, using statistical calculations from the SPSS program. Research Results: Based on the results of Bivariate Analysis with paired T-test with a sample size of 30 respondents (N=30), the data showed that T-Count (23.854) > T-table (0.462) and the p.Value (0.000) < alpha value ( 0.05) which means there is an influence between the back pain of pregnant women in the third trimester before and after being given prenatal massage at the Pebayuran Community Health Center Conclusions and Suggestions: After carrying out the Prenatal Massage, the majority of respondents who did not experience pain were 15 respondents (50.0%), 10 respondents had mild pain (33.4%), 5 respondents (16.6%) had moderate pain. .There is an influence between the back pain of pregnant women in the third trimester before and after being given prenatal massage at the Pebayuran Community Health Center.